Thanksgiving on Thursday / 27. - Osborne, Mary Pope (Magic tree house, 2002)
Jack and Annie travel in their magic treehouse to the year 1621, where they celebrate the first Thanksgiving with the Pilgrims and Wampanoag Indians in the New Plymouth Colony.